2016
DOI: 10.1002/app.43459
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of the rheological behaviors of polypropylene in a capillary flow

Abstract: The rheological characterization of polymer melts is strongly related to their material properties. In this study, we focused on the rheological behaviors of a polypropylene (PP) melt through a capillary die. With an advanced twin-bore capillary rheometer with dies measuring 1.0, 0.5, and 0.25 mm in diameter, experiments were performed over a shear-rate range of 3 3 10 2 to 5 3 10 3 s 21 at three temperatures, 210, 220, and 230 8C. The results demonstrate that the geometry dependence of the PP viscosity relied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…For the investigated PP/PMMA melts, the observed differences in the temperature sensitivity and geometric dependence of the shear viscosity are also in agreement with the analysis reported in our previous study . An increasing temperature leads to a decrease of viscosity, whereas an increasing pressure is linked to an increase in the viscosity of polymer melt.…”
Section: Resultsmentioning
confidence: 99%
“…For the investigated PP/PMMA melts, the observed differences in the temperature sensitivity and geometric dependence of the shear viscosity are also in agreement with the analysis reported in our previous study . An increasing temperature leads to a decrease of viscosity, whereas an increasing pressure is linked to an increase in the viscosity of polymer melt.…”
Section: Resultsmentioning
confidence: 99%
“…Bagley correction becomes unnecessary, as no inlet and outlet pressure losses occur. Meng et al [ 15 ] performed viscosity measurements of PP using various capillary diameters and showed that no wall slip occurs in a 1 mm capillary at 210–230 °C. In our experiments, we therefore assumed that the no-slip condition is valid, which also rendered a Mooney correction unnecessary.…”
Section: Methodsmentioning
confidence: 99%
“…Increasing temperature causes a decrease in shear stress, fracture strength and fracture strain. Meng et al 13 examined the effect of die diameter and operating temperature on the viscosity of recycled PP. A decrease in die diameter and operating temperature leads to an increase in the viscosity of recycled PP.…”
Section: Introductionmentioning
confidence: 99%